The effect of instructed dental flossing on interdental gingival bleeding: A randomized controlled clinical trial - Harris Basali, David. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Periodontology.; Advisor: Paul Levi Jr..; Committee: Guzin Uzel, Robert Gyurko, Mathew Finkelman, and Peter Arsenault.; Keyword: Dentistry.